A Self‐Binding, Melt‐Castable, Crystalline Organic Electrolyte for Sodium Ion Conduction. Issue 49 (9th November 2016) - Chinnam, Parameswara Rao; Fall, Birane; Dikin, Dmitriy A.; Jalil, AbdelAziz; Hamilton, Clifton R.; Wunder, Stephanie L.; Zdilla, Michael J.
Abstract: The preparation and characterization of the cocrystalline solid–organic sodium ion electrolyte NaClO4 (DMF)3 (DMF=dimethylformamide) is described. The crystal structure of NaClO4 (DMF)3 reveals parallel channels of Na + and ClO4 − ions. Pressed pellets of microcrystalline NaClO4 (DMF)3 exhibit a conductivity of 3×10 −4  S cm −1 at room temperature with a low activation barrier to conduction of 25 kJ mol −1 . SEM revealed thin liquid interfacial contacts between crystalline grains, which promote conductivity. The material melts gradually between 55–65 °C, but does not decompose, and upon cooling, it resolidifies as solid NaClO4 (DMF)3, permitting melt casting of the electrolyte into thin films and the fabrication of cells in the liquid state and ensuring penetration of the electrolyte between the electrode active particles. Abstract : The cocrystalline solid–organic sodium ion electrolyte NaClO4 (DMF)3 (DMF=dimethylformamide) features parallel channels of Na + and ClO4 − ions. The material melted gradually between 55–65 °C, but did not decompose, and it resolidified as solid NaClO4 (DMF)3 upon cooling. Pressed pellets of NaClO4 (DMF)3 exhibited a conductivity of 3×10 −4  S cm −1 at room temperature.